FAKTOR –FAKTOR YANG MEMPENGARUHI PEDAGANG KAKI LIMA BERJUALAN DI TROTOAR JALAN TUANKU TAMBUSAI KOTA PEKANBARU - Al Kahfi, Muhammad David; ", Jonyanis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research analyzes the factors and strategies of street vendors against the reform undertaken by the Government of the city of Pekanbaru. It is a social phenomenon that occurred in the community who have low economic income such as street vendors who sell in tuanku tambusai street sidewalks.The theory used in this research is the theory of Rational action, the concept of social capital, the concept of trust, and Government policy regarding public order and frame.Data analysis used in this research was qualitative with descriptive way. The technique of data collects in this research is Purposive, where informants as many as 10 people consisting of street vendors. The results of the research showed the real perception of street vendors who sell on jalan tuanku tambusai sidewalk gave positive responses. The government reform was done properly and well. However there is a small percentage that gives negative response by saying reform was not done nicely.In conducting the activities of trading, the street vendors have cause factor and also the strategy of maintaining the place when the reform is being done, such as doing resistance and building a network. Keyword : Street vendor, Factors, Strategy